1997
DOI: 10.1104/pp.113.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Phytochromes Are Involved in Red-Light-Induced Enhancement of First-Positive Phototropism in Arabidopsis thaliana

Abstract: The amplitude of phototropic curvature to blue light is enhanced by a prior exposure of seedlings to red light. This enhancement i s mediated by phytochrome. Fluence-response relationships have been constructed for red-light-induced enhancement in the phytochrome A (phyA) null mutant, the phytochrome B-(phyB) deficient mutant, and in two transgenic lines of Arabidopsis thaliana that overexpress either phyA or phyB. These fluence-response relationships demonstrate the existence of two responses in enhancement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 11 publications
4
63
0
Order By: Relevance
“…Both phyA and phyB have been shown to modulate phototropism in Arabidopsis (Parks etal. 1996;Janoudi & Poff 1997). First positive phototropism was found to be enhanced by phyA in response to very low-to-low fluence R (Parks et al 1996).…”
Section: Phytochrome and Phototropismmentioning
confidence: 93%
“…Both phyA and phyB have been shown to modulate phototropism in Arabidopsis (Parks etal. 1996;Janoudi & Poff 1997). First positive phototropism was found to be enhanced by phyA in response to very low-to-low fluence R (Parks et al 1996).…”
Section: Phytochrome and Phototropismmentioning
confidence: 93%
“…Whatever the exact mechanism, recent evidence that phyA is expressed in the root cap of Arabidopsis (Hall et al, 2001), where light sensing occurs, supports our observations that phyA plays a role in the root phototropic response. Furthermore, whereas the blue-light receptor family of phototropins (Briggs and Christie, 2002) function in light perception mechanisms of phototropism in stems and stem-like organs, phyA (Parks et al, 1996) and phyB (Janoudi and Poff, 1997) have been shown to regulate red-and far-red induction of phototropic enhancement in hypocotyls.…”
Section: Discussionmentioning
confidence: 99%
“…29 More recently, studies demonstrated that the phytochrome signaling component PHYTOCHROME KINASE SUBSTRATE 1 (PKS1) protein is required for hypocotyl phototropism in A. thaliana and PKS1 can form a complex with PHOT1 and NPH3. 30 Since phytochromes (and cryptochromes) influence phototropic curvature in A. thaliana as well, 31 PKS proteins may constitute a link between the photoreceptor families.…”
Section: Photoreceptorsmentioning
confidence: 99%